Beyond the Mega Events: “Useful” Policies for Urban Mobility - Ceudech, Andrea (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The paper analyses, through different examples, the limits of the urban mobility policies implemented for mega events, highlighting the tendency to privilege the infrastructure realization, more than policies on services, whose real usefulness is often put in doubt from the practice and whose maintenance often become a new cost for the community. On the base of a short review of the mobility policies mainly implemented in the preparation and management of the mega events, the paper highlights, from a critical point of view, the strengths and weaknesses of some experiences with reference to the real usefulness of urban mobility for the community beyond the mega event. The outcomes and the so-called “legacy” of the mega events for the cities are very different. Mega sport events, like the Olympic Games, have often involved only the realization of works for the event while events like the International Expositions have determined the acquisition of areas on which setting up the structures for the event. Only in few cases the works realized for the events have been inserted in a wider requalification or regeneration than programme involving the whole city and have been used as tools to achieve a stable improvement of the urban quality, above all regarding mobility. On the base of such considerations some aspects and key-points of urban mobility policies are highlighted in order to achieve real advantages to the community once the mega event is finished.